Adverse health events associated with antipsychotic use: an umbrella review - Chow, RTS (2021)
INTRODUCTION: Antipsychotic medications are prescribed in nearly 800,000 patients in England. Monitoring the adverse effects of antipsychotics is essential in the prevention of harm to patients. Numerous systematic reviews have found evidence for antipsychotics’ adverse effects, but few attempts have been made to assess the robustness of these evidence. This umbrella review aimed to grade and summarise the evidence for all adverse health events associated with antipsychotic use in the community settings, and assess the potential factors moderating the antipsychotic-adverse event associations, through the comparison across outcomes, quality assessments and identification of the current literature gaps.